APES: Acute Precipitating Electron Spectrometer—A high time resolution monodirectional magnetic deflection electron spectrometer. Issue 6 (7th June 2016) - Michell, R. G.; Samara, M.; Grubbs, G.; Ogasawara, K.; Miller, G.; Trevino, J. A.; Webster, J.; Stange, J.
Abstract: We present a description of the Acute Precipitating Electron Spectrometer (APES) that was designed and built for the Ground‐to‐Rocket Electron Electrodynamics Correlative Experiment (GREECE) auroral sounding rocket mission. The purpose was to measure the precipitating electron spectrum with high time resolution, on the order of milliseconds. The trade‐off made in order to achieve high time resolution was to limit the aperture to only one look direction. The energy selection was done by using a permanent magnet to separate the incoming electrons, such that the different energies would fall onto different regions of the microchannel plate and therefore be detected by different anodes. A rectangular microchannel plate (MCP) was used (15 mm × 100 mm), and there was a total of 50 discrete anodes under the MCP, each one 15 mm × 1.5 mm, with a 0.5 mm spacing between anodes. The target energy range of APES was 200 eV to 30 keV. Key Points: The APES instrument flew with a high time resolution of 9 ms Rapid changes in precipitating electron features can be resolved The APES instrument is versatile and can be adapted for many different uses